The Economic and Infrastructural Basis for the Development of Tourist Space: The Essence, Structure and Typology - DUNETS, Alexandr; LATYSHEVA, Olga; BITTER, Nataliya; VAKHRUSHEV, Igor; SHICHIYAKH, Rustem; ZHURULI, Georgiy (Journal of Environmental Management and Tourism; Vol 10 No 2 (2019): JEMT VOlume X Issue 2(34) Spring 2019DO - 10.14505//jemt.v10.2(34).05, 2019)
The article presents the approaches to the understanding of the tourism space and its structure. The purpose of the study is to identify the structural elements of the tourism space, which will allow conducting the analysis of the tourism development in the region. The methodological basis is the frame-based approach, which allows identifying the economic and infrastructural features of the tourism space. It is proposed to identify the types of the development of the tourism space on the basis of the analysis of its structure, the features of the functioning of tourism activities, as well as the development of the framework. On the example of the Altai-Sayan mountain region, the development of the tourism space is analyzed. The dimensional analysis of tourism development was conducted in the studied region. It is revealed that a decrease in the complexity of the tourism space and its component structures is observed from the north to the south, from the west to the east and from the periphery to the center. There are focal, linear and dispersed elements of the tourism framework in the structure of the tourism space. An areal form is also possible, which is typical for tourism areas. The structural elements of the tourism framework may have a different meaning for the development of tourism and vary depending on the size and tourism value. It is recommended to correlate the level of the development and the capacity of the tourism infrastructure with the tourism requirements. More detailed studies of the tourism space are important to reveal the influence of management actions on the economy and infrastructure of the territory, as well as their interrelation with the level of tourism development. Tourism space is a basic concept and it is considered important to understand its content and analyze the structure. The typology of tourism space is required for applying adequate mechanisms to its development.